38 What do undergraduates want in campus sexual assault prevention programming? findings from a formative research study. (19th September 2017) - Huang, Tiana; Philyaw-Kotov, Meredith L; Gleckman-Krut, Miriam; Davis, Alan K; Epstein-Ngo, Quyen M; Kusunoki, Yasamin; Bonar, Erin E
Abstract : Statement of purpose: Campus sexual assault is a significant public health issue, given its alarming prevalence and association with adverse physical, psychological, and economic outcomes. While many school-based sexual assault prevention intervention programs currently exist, few have strong empirical support in college settings. Consequently, there is a pressing need for formative research with undergraduate students to shape the development of relevant and effective, multi-pronged approaches for preventing sexual assault on college campuses. Methods: Full-time undergraduate sophomores at the University of Michigan were recruited via two registrar emails and campus flyers to participate in audio-recorded, semi-structured, one-on-one interviews (n=19) in June-November 2016. Participants were asked to provide feedback about desirable characteristics of sexual assault prevention programming, including intervention content, program format, and delivery mechanism. Interview audio files were transcribed and codes were generated using thematic analysis. Two trained Research Assistants (RAs) independently coded each theme using NVivo 11. Inter-coder reliability was assessed and coding discrepancies were resolved by a third coder. Results: Participant demographics (52.6% male, 57.96% White/Not Hispanic) resemble campus enrollment statistics. Further, 68.4% of participants reported lifetime sexual activity, and 42.1% were Greek Life-affiliated. Preliminary findings suggest that peer-based programming administered in-person to individuals or small, mixed-gender groups of unfamiliar students is more acceptable to undergraduates than other intervention formats (e.g., delivered in classes). Participants emphasised the importance of a forum where students can talk openly and seriously about sexual assault. Peer survivor testimonies and skits were mentioned as potentially effective ways to deliver content. Conclusions/Significance: As part of their sexual assault prevention education, college students welcome opportunities for discussions led by relatable peers who understand the dynamics of campus life. Our findings warrant future studies examining the effectiveness of campus-based, discussion-oriented sexual assault prevention intervention programs.